Literature Review: EFEKTIVITAS PENGGUNAAN GAME EDUKATIF DALAM MENINGKATKAN KETERAMPILAN MENULIS DI SEKOLAH DASAR - Maulidya Yasmin; Dinda Siti Hawa; Ichsan Fauzi Rahman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This study examines the effectiveness of educational games and language-based game methods in enhancing writing skills, literacy, numeracy, and character development among elementary school students through a literature review approach. The findings indicate that game-based learning media such as games, puzzles, Wordwall, and Android-based applications significantly improve students' motivation, active engagement, collaboration, and learning outcomes. Interactive activities such as sentence construction, story completion, and creating digital comics have been proven to help students develop ideas, enrich vocabulary, enhance language accuracy, and build selfconfidence in written communication. Despite challenges such as limited access to technology and lack of teacher understanding, with proper design and implementation, educational games have great potential to improve the quality of writing instruction and support holistic character development. These findings are expected to serve as a foundation for teachers and policymakers in more widely and effectively integrating educational games into the elementary education curriculum in Indonesia